The good left undone : [large type] a novel - Trigiani, Adriana (Random House Large Print, 2022)
"From present day Viareggio to Glasgow during World War II, a multigenerational sweeping tale of love lost, family secrets, and reconciliation over decades from New York Times bestselling author Adriana Trigiani"--